Yabiku strategy in handling domestic violence in North Central Timor District - Sanbein, Serli Mariani; Mbiri, Adeodata Laniria Charla Barros; Kolne, Yakobus (Journal of Law Science, 2025)
The focus of this study is the strategy for handling domestic violence by Yabiku. The data analysis technique used in this study is the Miles and Hubermans interactive model. The results of the study indicate that the strategy for handlinBibliographyg mechanisms is quite measurable and comprehensive, namely through various methods and actions. Among them are getting reports, picking up the ball, correspondence and telephone. At the level of supporting human resources, YABIKU NTT has an institutional structure of the Division for assisting women and children victims of violence, the Division for organizing women and natural resources, the Fundraising Division, Operational Manager, Admin and financial Manager. Based on the advocacy model carried out by YABIKU NTT, it is to synergize and partner with the government and the community to provide policies related to handling victims. That through strategic partnerships and efforts to mobilize the participation of the parties is very much needed in the integrated victim handling process. In addition, there are also three models and stages of legal advocacy in handling victims of violence. Handling cases of violence against women does not only focus on the legal aspect, but also helps them to recover, rebuild their lives and prevent violence from happening again. Therefore, cooperation between the parties is needed to empower women victims of violence from an economic and psychological perspective. In addition to regulations that support victims of violence, there is a need for funds and Standard Operating Procedures for the Referral System for handling cases.